SISTEM PAKAR DIAGNOSA KERUSAKAN MESIN ATM MENGGUNAKAN METODE CERTAINTY FACTOR PADA BANK UOB - Maula, Tezar; Gunadi, Goldie (Infotech: Journal of Technology Information, 2024)
Bank UOB (United Overseas Bank) Indonesia is a company operating in the banking industry. Some of the banking products provided by UOB include cards, savings, loans, investments and insurance. Apart from offering banking product services for individuals, UOB Indonesia also provides various banking products for corporations or business institutions. To provide the best service to its customers, currently UOB Indonesia has 142 ATMs spread throughout Indonesia. As business grows and the number of customers increases, transactions using ATMs increase rapidly. Disturbances and problems with ATM machines can result in a decrease in the level of customer satisfaction and loyalty towards UOB services. The solution to overcome this problem is to build a web-based expert system application that can be used to diagnose damage to NCR type ATM machines using the Certainty Factor method. In this research, application development was carried out using the PHP programming language and MySQL database. The benefit obtained from this application is that it makes it faster for UOB ATM technicians to determine damage to ATM machine equipment based on symptoms found during checking and then obtain the right repair solution. Because the application created is web-based so it can be accessed at any time from anywhere using a laptop or smartphone.ABSTRAKBank UOB (United Overseas Bank) Indonesia merupakan salah satu perusahaan yang bergerak di industri perbankan. Beberapa produk perbankan yang disediakan oleh UOB diantaranya adalah kartu, simpanan, pinjaman, investasi dan asuransi. Selain menawarkan layanan produk perbankan untuk perorangan UOB Indonesia juga menyediakan berbagai produk perbankan untuk korporasi atau institusi bisnis. Untuk memberikan pelayanan yang terbaik kepada para nasabahnya, saat ini UOB Indonesia memiliki 142 ATM yang tersebar di seluruh Indonesia. Seiring dengan pertumbuhan bisnis dan bertambahnya jumlah nasabah maka transaksi menggunakan ATM meningkat pesat. Gangguan dan kendala pada mesin ATM dapat mengakibatkan menurunnya tingkat kepuasan dan loyalitas nasabah terhadap pelayanan UOB. Solusi untuk mengatasi permasalahan tersebut adalah dengan membangun sebuah aplikasi sistem pakar berbasis web yang dapat dimanfaatkan untuk melakukan diagnosis kerusakan mesin ATM bertipe NCR menggunakan metode Certainty Factor. Dalam penelitian ini pengembangan aplikasi dilakukan dengan bahasa pemrograman PHP dan basis data MySQL. Manfaat yang diperoleh dari aplikasi ini adalah mempercepat teknisi ATM UOB menentukan kerusakan perangkat mesin ATM berdasarkan gejala yang ditemukan saat pengecekan dan kemudian memperoleh solusi perbaikan yang tepat. Karena aplikasi yang dibuat  berbasis web sehingga dapat diakses setiap saat dari mana saja dengan menggunakan perangkat laptop maupun smartphone.